Work-text in general physics 2 for senior high school - Reyes, Cristopher G. (Quezon City : Great Books Trading, 2018)
This book is the continuation course of General Physics 1 in the Senior High School which leads you to the study of the common branches of physics that are been divided into Mechanics, Heat, Sound, Optics, Electricity, Magnetism, and Modern Physics.
Includes appendices and reference.
Keywords: Physics